Respon Tanaman Pakcoy (Brassica rapa L.) Terhadap Kombinasi Abu Janjang Kelapa Sawit dan Pupuk NPK di Medium Gambut - Rian Triono; Arnis En Yulia; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aimed to determine the response of the pakcoy plant to the combination of the AJKSand NPK fertilizer and to get the best combination of the growth and production of pakcoy (Brassica rapa L.) in peat medium. The research has been conducted in Experimental Field of Faculty Agriculture of Riau University from March to April 2017. This research was conducted experimentally with Factorial Completely Randomized Design  which consisting of 2 factors and 3 replications. The first factor of dose of AJKS 2, 4, 6    tons/ha, second factor of dose NPK was  200, 250, 300 kg/ha. The data have been statistically analyzed and Tukey's 5%. The results showed that the combination of AJKS and NPK significantly increased leaf area, fresh weight of plants and had no significant effect on plant height, leaf number and consumption fresh weight. Implementation of6 tons/ha AJKS and 300 kg/ha NPK fertilizer is the best dose to increase the growth and production of pakcoy plant.Keyword: Pakcoy, peat, AJKS, NPK fertilizer